The Concept of Problem and Solution Management in Guidance and Counseling - Putra Suharnadi; Neviyarni S; Yarmis Sukur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Educational management is the art and science of managing educational resources to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble character and skills needed by themselves, society, nation and state. Management needs are certainly inseparable from the basic concept of management in general, especially management functions, because leaders or managers must go through a series of events, Management functions include: Planning, Organizing, Staffing, Monitoring, Controlling. in order to carry out BK services as optimally as possible, in addition to forming and managing the organization well and assigning personnel according to their respective abilities, several facilities and infrastructure or facilities are needed to support the implementation of correct and effective BK services. The purpose of this study was to determine the Concept of Problem Management and Solutions in Guidance and Counseling. Research method, namely This study uses a qualitative descriptive approach with a case study research type. Qualitative methods are used to understand the meaning of social or humanitarian problems that are considered important by a group of people. The results of this study are that the management of BK teachers or counselors in schools has an important role in increasing the efficiency and effectiveness of BK services. Through the implementation of proper management, BK teachers can facilitate an active, creative, innovative, and enjoyable learning process for students.